MODEL PENDIDIKAN KARAKTER MELALUI SISTEM FULL DAY SCHOOL DAN PENDIDIKAN TERPADU (Studi Kasus di Sekolah Dasar Islam Terpadu Al-Hidayah Pangarangan Sumenep) - Iwan Kuswandi (Reflektika, 2015)
The number of crimes that occur among teenagers is evidence of the low character possessed by them. It seems unwise to only blame it because of the impact of globalization. As a nation that has a history of civilization like other eastern nations. Character is something that should get attention. Of course the role of education is highly expected on this issue. Lately, a solution that is considered to be a bit capable of solving the thorny problem above, is through a full day school system and integrated education. In this paper, we will examine character education through a full day school system and integrated education at Al-Hidayah Sumenep Integrated Islamic Elementary School, with a focus on how to implement character education at Al-Hidayah Pangarangan Sumenep Integrated Islamic Elementary School? And what is the character education model through a full day school system and integrated education at the Al-Hidayah Pangarangan Sumenep Integrated Islamic Elementary School? The method used is descriptive qualitative, with data collection techniques used in this study are: (a) Observation, (b) Interview, (c) Documentation Study. By using qualitative analysis. The results of this study found that the implementation of character education at Al-Hidayah Pangarangan Sumenep Integrated Islamic Elementary School used a full day school system and integrated education. Education starts at 07.00 WIB, starting with memorizing the Qur'an in the first hour. Teaching and learning activities end at 15.30 WIB, in which it is obligatory to attend the Dhuhr and Asr prayers. Meanwhile, the character education model is through a full day school system and integrated education at the Al-Hidayah Pangarangan Sumenep Integrated Islamic Elementary School. In accordance with the results of the study that the character education provided stems from the values of the Koran, education and character building, not only carried out while at school, but teachers also actively visit the homes of each of their students.